Activation Strategies and the Performance of Employment Services in Germany, the Netherlands and the United Kingdom - Tergeist, Peter (OECD Publishing, 2006)
Strategies to 'activate' the unemployed with the help of high-quality employment services have continuously gained importance in the policy debate. The purpose of this report is to examine how activation strategies and the performance of employment services are addressed in three countries which have undertaken considerable reforms in recent years, namely Germany, the Netherlands and the United Kingdom. All three review countries have implemented a 'mutual obligations' approach
Keywords: Social Issues/Migration/Health; Germany; Netherlands; United Kingdom